The State Defense Legal Politics: National Protection Based on Pancasila Justice - Budi Pramono; Ahmad Salim; Noor Lailatul Izza; Mega Arum Saputri; Lutter Ariestino (Jurnal Hukum, 2025)
Indonesia's national defense legal policy must be built adaptively and based on Pancasila and the 1945 Constitution, by integrating military and non-military defense through a participatory, layered defense strategy. The purpose of this study is to analyze national defense regulations within the concept of the unitary state of the Republic of Indonesia and analyze national defense legal policy based on Pancasila justice. This research is based on Normative Law research. A Pancasila-based national defense legal policy emphasizes moral, humanitarian, and democratic values in building an inclusive, participatory, and adaptive defense system, while adopting strategic elements from global practices to enhance Indonesia's sovereignty and resilience amid evolving global threats. The novelty of this approach lies in integrating Pancasila's ethical and philosophical values as the foundational framework for national defense policy, shifting the focus from purely militaristic strategies to a holistic, people-centered security model. Additionally, it introduces an innovative blend of global best practices such as China’s technological integration, Scandinavia’s participatory governance, and Japan’s diplomatic defense stance while maintaining Indonesia’s unique identity rooted in social justice and sovereignty.